2001
DOI: 10.1074/jbc.m004477200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chromosome Region Maintenance 1-independent Nuclear Export Signal of the Large Form of Hepatitis Delta Antigen That Is Required for the Viral Assembly

Abstract: Hepatitis delta virus (HDV) is a satellite virus of hepatitis B virus, as it requires hepatitis B virus for virion Hepatitis delta virus (HDV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 42 publications
5
99
0
Order By: Relevance
“…On the other hand, neither BFA nor wortmannin affected the assembly of small HBsAg. According to the findings from the current study and our previous studies (24,47), we propose that small HBsAg may form 22-nm subviral particles at post-ER, pre-Golgi (intermediate) membranes and/or proximal Golgi membranes, but not TGN, and secrete from cells. On the other hand, HDAg-L forms complexes with HDAg-S and viral genomic RNA (vRNPs) in the nucleus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, neither BFA nor wortmannin affected the assembly of small HBsAg. According to the findings from the current study and our previous studies (24,47), we propose that small HBsAg may form 22-nm subviral particles at post-ER, pre-Golgi (intermediate) membranes and/or proximal Golgi membranes, but not TGN, and secrete from cells. On the other hand, HDAg-L forms complexes with HDAg-S and viral genomic RNA (vRNPs) in the nucleus.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, in the presence of small HBsAg, HDAg-L localizes to both the nucleus and the cytoplasm. A nuclear export signal (NES) at the unique C terminus of HDAg-L was identified (24). Recently, we also identified a cellular protein, NESI, which specifically interacts with the NES of HDAg-L and is essential for HDAg-L-mediated nuclear export of HDV RNA (47).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The nuclear export of genomic HDV RNA may be related to the virion assembly process and may not be part of HDV RNA replication per se. If this is so, it might be expected that its export would be dependent on the presence of LHDAg, as suggested by a recent study (11). To address this question, we constructed a mutant HDV genome similar to that described in an earlier study (2), in which a uridine nucleotide was inserted immediately after the UAG stop codon for S-HDAg.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since HBsAg is present only in the cytoplasm and HDV RNA replication occurs in the nucleus, the nuclear export of genomic HDV RNA at certain points of the viral replication cycle must also be required. It has been suggested that this is dependent on L-HDAg, which contains a nuclear export signal near the COOH terminus (11). However, the role of this signal in RNA packaging has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%